2022
DOI: 10.1186/s12957-022-02775-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative low absolute lymphocyte count to fibrinogen ratio correlated with poor survival in nonmetastatic colorectal cancer

Abstract: Background Preoperative absolute lymphocyte count (LC) and fibrinogen (FIB) are useful prognostic indicators in colorectal cancer (CRC). However, the prognostic value of the LC to FIB ratio (LFR) has never been addressed. Methods A total of 189 nonmetastatic CRC patients after resection were enrolled retrospectively. The significance of the LFR in predicting disease-free survival (DFS) and overall survival (OS) was estimated by receiver operating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Two different types of scores have been proposed to track the systemic inflammatory response: those based on protein measurement and those based on inflammatory cell counting. Patients with CRC can have their condition predicted by counting these differentiated cells individually or collectively [ 46 , 47 , 48 , 49 , 50 ]. Studies evaluating the relationship between NLR and various cancers have shown that it was a strong prognostic factor [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two different types of scores have been proposed to track the systemic inflammatory response: those based on protein measurement and those based on inflammatory cell counting. Patients with CRC can have their condition predicted by counting these differentiated cells individually or collectively [ 46 , 47 , 48 , 49 , 50 ]. Studies evaluating the relationship between NLR and various cancers have shown that it was a strong prognostic factor [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Routine laboratory tests and the method to measure blood cell fractions were performed as described previously [ 19 , 20 ]. The CRP (reference: 0-0.5 mg/dl) was measured by using turbidimetric inhibition immunoassay with the CRPL3 kit (Roche Diagnostics GmbH, Mannheim, Germany) according to the manufacturer’s manual with the automatic analysis system (Cobas e 501, Roche, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Cases meeting any one of the following criteria were excluded: 1. any preoperative anticancer therapies; 2. suspected distant lesions identified by imaging examinations; 3. complications that require long-term administration of anticoagulant drugs, such as aspirin and Plavix; 4. lack of preoperative laboratory tests, such as DD; 5. absence of postoperative pathological TNM message; and 6. follow-up problems. Parameters including age, sex, tumor location and others were also recorded as previously described [ 35 , 36 ]. The study was approved by the ethics committee of Hainan Hospital of Chinese PLA General Hospital (ID: 301HLFYLS15), and informed consent was obtained from the patients or their authorized relatives.…”
Section: Methodsmentioning
confidence: 99%
“…Routine blood tests were conducted in the departmental clinical laboratory as previously described [ 35 ]. The reference was 35–50 g/L for serum albumin, 1.75–7.00 × 10 9 /L for peripheral absolute lymphocyte counts, and 0–500 ng/mL for DD levels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation